Antibacterial activity and susceptibility testing of bacterial isolates from nematodes (Cruznema spp.) - Mothapo, Maletjema Magdeline (University of the Witwatersrand, Johannesburg, 2023)
Nematodes are unsegmented worms found in different niches associated with a diverse range of bacteria. Various types of nematodes exist including those that are parasitic to insects, known as entomopathogenic nematodes (EPNs). EPNS of genera Steinernema, Heterorhabditis and Oscheuis are symbiotically associated with Xenorhabdus, Photorhabdus and Serratia, respectively. The symbiotic bacteria of EPNs have been reported to produce a broad spectrum of antimicrobial compounds active against human pathogens. The aim of this study was to isolate and identify nematodes and their associated bacteria from soil samples collected from a vegetative farm in Lesotho and study their antimicrobial activity against four species of pathogenic bacteria (E. coli, S. aureus, E. faecalis and P. aeruginosa). An uncharacterized species of Cruznema was isolated and named Cruznema NTM-2021 (GenBank 18S rDNA accession number: OQ408141). Based on the BLASTN search incorporating the phylogenetic analysis of the 16S rDNA region, three genera of bacteria were identified as Alcaligenes sp., Enterobacter sp. and Elizabethkingia sp. The study revealed that all three bacterial isolates were pathogenic to Tenebrio molitor. Symbiosis tests, using lipid agar method demonstrated the ability of the host nematodes to develop and reproduce in the presence of their associated bacteria. Bacterial supernatants of Alcaligenes sp. and Enterobacter sp. showed some inhibitory activity against Escherichia coli and Enterococcus faecalis, by disk diffusion method. Staphylococcus aureus and Pseudomonas aeruginosa were the most resistant bacteria to supernatants of the three isolates. This study also showed that the Alcaligenes, Enterobacter, and Elizabethkingia species isolated from Cruznema NTM-2021 were resistant to ampicillin, amoxicillin, cefuroxime/sodium, vancomycin and cephalothin but susceptible to gentamicin.
Dissertation Submitted in fulfilment of the requirements for the degree of Master of Science degree (in Microbiology and Biotechnology), to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Antibacterial activity; Susceptibility testing; Cruznema spp; UCTD; SDG-3: Good health and well-being